Reactive oxygen species and aldehyde dehydrogenase activity in Hodgkin lymphoma cells - Ikeda, Jun-ichiro; Mamat, Suhana; Tian, Tian; Wang, Yi; Luo, Wenjuan; Rahadiani, Nur; Aozasa, Katsuyuki; Morii, Eiichi (Nature Publishing Group, 2012)
Tumor cells with tumorigenic potential might be limited to a small population of cells, called cancer-initiating cells (CICs). CICs efficiently form colonies in vitro, yield both CIC and non-CIC populations, maintain reactive oxygen species (ROS) at low levels, show high aldehyde dehydrogenase (ALDH) activity, and are mostly in a quiescent state of the cell cycle. CICs of Hodgkin lymphoma (HL) are small in size, with low levels of ROS. The relationship between ROS level and ALDH activity in CICs was examined in HL cell lines. ROS-low and ALDH-high populations formed colonies in semi-solid cultures more efficiently than ROS-high and ALDH-low populations. ALDH-high populations yielded both ALDH-low and -high populations, whereas ALDH-low populations rarely yielded an ALDH-high population. The number of cells in a quiescent state was significantly greater in ROS-low than in ROS-high cells, whereas that of ALDH-high and ALDH-low cells was comparable to each other. These findings show that ALDH-high and ROS-low cells share CIC-like potential, but they differ in their cell cycle status, suggesting that CICs are comprised of cells with heterogeneous characteristics.